(untitled) (Journal of Pharmaceutical Negative Results, 2022)
"Neglected posterior dislocation of the elbow" is described as an untreated traumatic posterior dislocation of the elbow joint that hasbeen untreated for 3 weeks or more. Around 90% of these are of the posterolateral variety. In emerging and underdeveloped countries,these are far more widespread. Patients report with a distorted, stiff, and painful elbow that makes it difficult to perform daily activities.The clinical presentation resembles that of a malunited supracondylar elbow fracture. Radiography is generally used to confirm thediagnosis. Before undergoing surgery, a CT or MRI scan is recommended to provide extra information. Because of the severe softtissue contractures, ligamentous insufficiencies, and fibrosis, as well as the possibility of accompanying nerve injuries, myositisossificans, non-compliant patients, and the necessity for long-term postoperative physiotherapy, treatment is difficult. The goal ofsurgical treatment is for the elbow to be painless, stable, and flexible, with a congruent joint space. We reported a case of 55-year-oldwoman presented to the Acharya Vinoba Bhave Rural Hospital (AVBRH) with complaints of inability to flex the elbow, inability tomake a fist, and tingling feelings in all five fingers on the left side, which had been bothering her for two months.